That Dragon, Cancer – dokument osobisty w formie gry komputerowej - Justyna Król (Images)
The article focuses on the That Dragon, Cancer, a computer game created by Amy and Ryan Green, which is about their son Joel’s disease and subsequent death. It analyses the means used to tell the story and deliver the emotions of the game’s authors: documentary elements and means of expression exclusive to the game medium (conscious use of failure, a form based on vignette games). It addresses the contexts of personal documentaries, their self-therapeutic aspect, and the phenomenon of “not-games” and “personal games”.